OTONOMI DAN AGENSI GURU PAI DALAM REKONSTRUKSI STRUKTUR ALUR TUJUAN PEMBELAJARAN (ATP) - Sofiana Sholikah; Dinifath Fitriani; Muhamad Faizal Aqila Akbar; Imam Junaris (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The implementation of the independent curriculum provides teachers with greater autonomy in developing learning objectives, but studies on the transformation of autonomy into teacher agency in Islamic religious education are still limited. This study aims to analyze the manifestation of Islamic religious education teacher autonomy, the role of the epistemological character of Islamic religious education in the reconstruction of the learning objectives, and the development of teacher agency in the implementation of the independent curriculum. The study used a systematic literature review approach with PRISMA 2020 guidelines. Data were obtained through Google Scholar using Publish or Perish version 8 for empirical articles from the 2022-2025 period. Four articles that met the inclusion criteria were analyzed using thematic synthesis. The results show that the reconstruction of the learning objectives is still dominated by an administrative orientation, resulting in the epistemological character of Islamic religious education not being optimally utilized. Teacher agency develops gradually from planning to implementation of learning, but has not been fully integrated through assessment and reflection. This study produces a conceptual framework for the reconstruction of the learning objectives flow based on teacher agency that integrates teacher autonomy, the epistemological character of Islamic religious education, and pedagogical reflection as a continuous learning development cycle.